2018
DOI: 10.5194/acp-18-2381-2018
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-(208–318 K) and pressure-(18–696 Torr) dependent rate coefficients for the reaction between OH and HNO<sub>3</sub>

Abstract: Abstract. Rate coefficients (k5) for the title reaction were obtained using pulsed laser photolytic generation of OH coupled to its detection by laser-induced fluorescence (PLP–LIF). More than 80 determinations of k5 were carried out in nitrogen or air bath gas at various temperatures and pressures. The accuracy of the rate coefficients obtained was enhanced by in situ measurement of the concentrations of both HNO3 reactant and NO2 impurity. The rate coefficients show both temperature and pressure dependence w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 50 publications
3
32
2
Order By: Relevance
“…In the same experiment, we also recorded the optical density at 285 185 nm where H2O, NO2 and HNO3 all absorb. Despite the large HNO3 absorption cross-section at this wavelength (1.6 × 10 -17 cm 2 molecule -1 , Dulitz et al (2018)) we found no evidence for HNO3 formation, indicating that the NO2 lost was not converted to gas-phase HNO3. Given its great affinity for glass in the presence of H2O, we expect that any HNO3 formed is strongly partitioned to the walls of the reactor.…”
Section: Parameterisation Of K1 From Data Obtained In N2-h2o and He-hcontrasting
confidence: 61%
“…In the same experiment, we also recorded the optical density at 285 185 nm where H2O, NO2 and HNO3 all absorb. Despite the large HNO3 absorption cross-section at this wavelength (1.6 × 10 -17 cm 2 molecule -1 , Dulitz et al (2018)) we found no evidence for HNO3 formation, indicating that the NO2 lost was not converted to gas-phase HNO3. Given its great affinity for glass in the presence of H2O, we expect that any HNO3 formed is strongly partitioned to the walls of the reactor.…”
Section: Parameterisation Of K1 From Data Obtained In N2-h2o and He-hcontrasting
confidence: 61%
“…NO 2 concentrations were calculated using a literature reference spectrum (Vandaele et al, 1998). Concentrations of HNO 3 and H 2 O were calculated using cross sections of 1.61×10 −17 cm 2 molecule −1 (Dulitz et al, 2018) and 7.22× 10 −20 cm 2 molecule −1 (Creasey et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…More than 10 years later, Li et al (2008) carried out similar experiments but at longer wavelengths (560-640 nm) and reached very different conclusions, deriving a yield of OH (and thus also HONO) close to 1×10 −3 , a factor of 14 larger than the upper limit of Crowley and Carl (1997). Calculations of the impact of Reactions (R4)-(R5) using the large yield reported by Li et al (2008) led to the conclusion that Reaction (R5) is important for air quality under highly polluted conditions; use of the lower yield from Crowley and Carl (1997) resulted in minimal impact (Wennberg and Dabdub, 2008;Ensberg et al, 2010). Subsequent to the work of Li et al (2008), two further experimental studies (Carr et al, 2009;Amedro et al, 2011) appeared to confirm the conclusions of Crowley and Carl (1997) and suggested that the high yield reported by Li et al (2008) was an experimental artefact, resulting from multiphoton laser excitation of NO 2 in their focussed laser beam (Amedro et al, 2011).…”
Section: No * 2 + H 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…secondary reactions of OH on the determination of k5. For the OH + NO2 reaction, the use of OH concentrations as high as 10 12 molecule cm -3 is not expected to have a significant impact on the OH decay rates because the major product, HNO3, reacts only slowly with OH with k(OH + HNO3) = 1.6 × 10 -13 cm 3 molecule -1 s -1 at 296 K and 250 Torr (Dulitz et al, 2018). Even if the minor product, HOONO, were to react with OH with a rate coefficient of close to 2 × 10 -10 cm 3 molecule -1 s -1 (i.e.…”
Section: Rate Coefficients For Oh + No2 (K5)mentioning
confidence: 99%